Future-proofing : making practice-based IT design sustainable - Simone, Carla; Wagner, Ina, 1946-; Müller, Claudia (Professor of information technology); Weibert, Anne; Wulf, Volker (Oxford University Press, 2022)
'Future-Proofing' addresses the problems of sustainability in IT research projects. It provides a conceptual framework which allows readers to better understand sustainability issues, make them aware of the challenges around effective sustainability, and provide tangible suggestions for researchers to put into action.
Also issued in print: 2022.
Keywords: Information technology -- Research.; Information technology projects -- Case studies.; elektronické knihy; electronic books